Anxiety of influence : Bahcelors, brides and a family romance. - Budak, Adam; Engel, Beate; Knüsel, Pius; Szczerski, Andrzej; Cisar, Karel; Piotrowski, Piotr; Kolecek, Michal; Bencsik, Barnabás; Stadtgalerie, Bern (Bern : Stadtgalerie, 2004)
Klimova, Barbora ; Kozyra, Katarzyna ; Lee, Tim ; Lejman, Dominik ; Ondreicka, Boris ; Lehocka, Denisa ; Schneemeier, Andrea ; Vleeschouwer, Kris
Stadtgalerie Bern in collaboration with Kunstmuseum Bern and Schlachthaus Theatre Bern, Bern, 23rd of April - 23rd of May, 2004
kunstcatalogus